Relationship between net photosynthesis and leaf respiration in Mediterranean evergreen species (Photosynthetica, 2008)
The relationship between net photosynthetic (PN) and leaf respiration (R) rates of Quercus ilex, Phillyrea latifolia, Myrtus communis, Arbutus unedo, and Cistus incanus was monitored in the period February 2006 to February 2007. The species investigated had low R and PN during winter, increasing from March to May, when mean air temperature reached 19.2 °C. During the favourable period, C. incanus and A. unedo had a higher mean PN (16.4±2.4 µmol m −2 s −1 ) than P. latifolia, Q. ilex, and M. communis (10.0±1.3 µmol m −2 s −1 ). The highest R (1.89±0.30 µmol m −2 s −1 , mean of the species), associated to a significant PN decrease (62 % of the maximum, mean value of the species), was measured in July (mean R/PN ratio 0.447±0.091). Q10, indicating the respiration sensitivity to short-term temperature increase, was in the range 1.49 to 2.21. Global change might modify R/PN determining differences in dry matter accumulation among the species, and Q. ilex and P. latifolia might be the most favoured species by their ability to maintain sufficiently higher PN and lower R during stress periods.